Interwoven : How the Better Work Program Improves Job and Life Quality in the Apparel Sector - World Bank (Washington, DC, 2015)
The Better Work Program has its roots in the Better Factories Cambodia (BFC) program, established in 2001 as a follow-on from the 1999 U.S.-Cambodia Bilateral Trade Agreement. The free trade agreement (FTA) was the first to link improved labor conditions with greater market access. The BFC program benefitted all the key stakeholders by improving work conditions, supporting the growth of the apparel sector in Cambodia (benefitting all local stakeholders), and boosting developed world buyers’ reputation by sourcing from ethical workplaces. BFC has also helped to cushion the negative effects of external changes to the trading environment in the apparel sector (the end of the Multi-Fibre Arrangement quota system in 2005 and the global financial crisis in 2008–09). The program has grown substantially; as of December 2014, BW has reached over a million workers in more than 1,000 factories across eight countries (Bangladesh, Cambodia, Haiti, Indonesia, Jordan, Lesotho, Nicaragua, and Vietnam).